Employee involvement in Decision Making on Performance of SME’s in Kitale, Trans Nzoia County, Kenya - W. Chesoli, Dr. Joshua (IJRDO - Journal of Business Management, 2018)
This study examined the effect of employee involvement in decision making on performance of selected SMEs in Kitale. Data was sourced from one hundred and twenty nine (129) employees and twenty seven (27) owner/managers of the randomly selected SMEs, with the aid of questionnaire. The datagenerated were statistically analyzed using descriptiveinferential statistical tools.  Results  showed  that’ on overall,  employee  participation  in  decision making  had significantpositive  impact  on organizational performance  in the SMEs, with (β = 0.597, t = 6.572, P<.01).The implication of this finding is that Kenyan SMEs should pay attention to human resource management practices which, they have hitherto, largely ignored, in the course of running their businesses. Increasing employee involvement in decision making will impact positively on their growth and potential for survival.